Exploring the asymmetric effects of economic policy uncertainty and implied volatilities on energy futures returns: novel insights from quantile-on-quantile regression - Bossman, Ahmed; Gherghina, Ştefan Cristian; Asafo-Adjei, Emmanuel; Adam, Anokye Mohammed; Agyei, Samuel Kwaku (Journal of Business Economics and Management, 2022)
This study examined the asymmetric effects of major uncertainty and volatility indices (economic policy uncertainty, Chicago Board Options Exchange crude oil volatility, CBOE volatility index, CBOE VIX volatility, and NASDAQ 100 volatility target) on the returns of global energy and its constituents (global energy index, Brent, heating oil, natural gas, and petroleum). The causalityin-quantiles test and the quantile-on-quantile regression technique were employed on daily data covering the period between April 2012 and March 2022. The findings evidenced asymmetries and heterogeneity in the causal effects of global uncertainty and market volatilities on energy markets. For all uncertainty and volatility measures, we found strong negative relationships with energy commodities at stressed conditions, signalling some hedging benefits for market participants. The current research is among the first investigations to explore the asymmetric relationships between major uncertainty and volatility indices, as well as global energy and its constituents. Essential portfolio implications of our findings are discussed.